Employee Performance Assessment Decision Support Using Profile Matching Method Compared to Simple Additive Weight Addition at Dharma Buddhi University, Tangerang - Muhammad Subhana; Yakub Yakub (Komunitas Dosen Indonesia, 2019)
An employee performance evaluation of the Buddhist Dharma University is needed to see the potential of its human resources. To get an employee performance appraisal in one year requires a decision support system that is fast and measurable so that the information obtained is accurate. The method used in assessing employee performance uses profile matching and is compared with the SAW (simple additive weight) method so that the results can be properly compared. The purpose of employee appraisal is so that leaders can easily obtain information about employee performance ratings at Buddhii Dharma University. The results of the value using the profile matching method can be recommended for salary increases and positions of 4 employees. Which can be recommended for salary increases there are 17 employees and those who are not eligible for salary increases and positions are valued at 12 employees. And comparing with the Simple Additive Weight (SAW) method, there are 19 employees who are eligible to raise salaries and 14 employees who are not eligible to raise salaries and positions